X-ray Photoelectron Spectroscopy for Probing Non-bridging Oxygen in Silver Ion Conductors and their Relationship to Ionic Conductivity - E.B, Saniman; M.Z.A, Yahya; A.K, Arof (Malaysian Journal of Science, 2002)
The materials studied in this work are 60AgI-20Ag$_{2}$O-20[0.1M$_{m}$O$_{n}$ + 0.9MÃ¢â‚¬â„¢$_{m'}$O$_{n'}$] of the boron oxide rich glass with M$_{m}$O$_{n}$ as WO$_{3}$ and MÃ¢â‚¬â„¢$_{m'}$O$_{n'}$ as B$_{2}$O$_{3}$ and the WO$_{3}$ rich glass with M$_{m}$O$_{n}$ as B$_{2}$O$_{3}$ and MÃ¢â‚¬â„¢$_{m'}$O$_{n'}$ as WO$_{3}$. XPS has shown that for glasses with the same amount of network modifiers glasses with a higher electrical conductivity have a larger number of (non-bridging oxygen) NBOs. This experiment helped in the deduction of the formation of tetrahedral oxyanions which when share corners with one another could result in the formation of larger channel-like pathways or Ã¢â‚¬Å“open structuresÃ¢â‚¬Â in the glasses through which more silver ions can flow through with ease.